Arbuscular mycorrhizal fungi reduce N2O emissions from degraded residue patches - Li, Xia; He, Guang; Li, Dandan; Bei, Shuikuan; Luan, Dongdong; Sun, Xinzhan; Yang, Gaiqiang; Huo, Lijuan; Zhen, Lina; Zhao, Ruotong (Frontiers in ecology and evolution, 2023)
Nitrous oxide (N 2 O) is a potent greenhouse gas, and agricultural soils represent a major anthropogenic source. Crop residues provide nutrients for plants but also act as hotspots of N 2 O production. The hyphae of arbuscular mycorrhizal fungi (AMF) could proliferate in organic patches, utilize released N from the organic patches, and potentially mitigate N 2 O emissions. However, the effect of AMF on N 2 O emissions in degraded residue patches and the possible microbial mechanism remain uncertain. Here, a mesocosm experiment was conducted to investigate the impact of AMF ( Funneliformis mosseae ) inoculation on N 2 O emissions, availabilities of carbon and nitrogen, extracellular enzyme activities, and the abundance of key N-cycling genes in degraded residue patches. Our results showed that AMF hyphae significantly reduced N 2 O emissions from degraded residue patches. Quantitative PCR analysis of key functional genes involved in N 2 O production ( amoA , nirK , nirS ) and consumption ( nosZ ) showed that AMF significantly reduced the abundance of the bacterial amoA and nirS genes. NH 4 + , NO 3 − , total dissolved nitrogen (TDN), total nitrogen (TN), and dissolved organic carbon (DOC) contents decreased drastically in the presence of AMF. In addition, the activities of all tested extracellular enzymes were significantly decreased by AMF and positively correlated with DOC content. Multiple stepwise regression analysis demonstrated that the abundance of the nirS gene primarily influenced N 2 O emissions and was positively correlated with DOC content in degraded residue patches. Our findings indicate that AMF suppressed N 2 O producers, particularly nirS -type denitrifiers, by slowing down the release of C and N from degraded residues, thereby leading to a cascade effect on the decrease of N 2 O emissions. This study provides a promising approach to mitigate N 2 O emissions by enhancing AMF in the agroecosystems.